INDONESIAN-ENGLISH CODE-SWITCHING IN ONLINE COMMUNICATION: TYPES, REASONS, AND DIGITAL IDENTITY - Nur Zanah Kaluku; Ica Natasya R.D. Husain; Sri Cily A. Bisale; Widyastuti WS. Harunja; Febryyana Ismi Ibrahim; Muziatun Mukadji (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study examines the patterns of Indonesian-English code-switching in digital communication among general social media users across four platforms: Instagram, TikTok, X (Twitter), and WhatsApp. In contemporary digital environments, bilingual users frequently alternate between languages to communicate and express their identities online. This study aims to identify the structural types of code-switching and explore their communicative motivations. Employing a qualitative descriptive design, the research analyzed forty linguistic data points collected from social media posts, comments, and chats. Poplack’s (1980) typology was used to classify the structural types of code-switching, while Myers-Scotton’s (1993) Markedness Model was applied to interpret their communicative functions. The findings reveal that intra-sentential switching is the most dominant type (65%), followed by inter-sentential switching (25%) and tag switching (10%). The analysis shows that code-switching functions as a strategy for identity expression, rhetorical emphasis, social connection, and participation in global digital culture. These findings suggest that language alternation is not merely a result of linguistic limitations but a deliberate communicative resource employed by bilingual users in digital interaction.